Close encounters : essays on Russian literature - Jackson, Robert Louis (Ars Rossika., 2013)
Close Encounters: Essays on Russian Literature combines discussions of ethical, esthetic, and philosophical interest raised by Pushkin, Gogol, Turgenev, Dostoevsky, Tolstoy, and Gorky, with close analyses of their texts. This book focuses on four thematic configurations: first ("Chance and Fate"), issues of freedom and responsibility, the necessity of free individual expression and yet the limits of will, or self-will; second ("Two Kinds of Beauty"), the unity of moral, esthetic, and spiritual categories, and the quest for the ideal; third ("Critical Perspectives"), examples of the type of commentary that approaches art with a unified ethical and spiritual perspective (Dostoevsky, Gorky, V.I. Ivanov, and the partially dissenting Bakhtin); and fourth ("Poems of Parting"), three poems (works by Tyutchev, Severyanin, and Pushkin) involving parting, loss, and recovery